2009
DOI: 10.1111/j.1538-7836.2009.03598.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of bleeding or thrombosis after polypectomy in patients receiving and not receiving anticoagulation therapy

Abstract: Summary. Background and aims: To assess the effect of warfarin anticoagulation therapy (AC) on the incidence of colon bleeding after elective colonoscopy with polypectomy and to identify independent predictors of post-polypectomy colon bleeding. Methods: This was a retrospective cohort analysis. Patients interrupting warfarin AC therapy for polypectomy (AC group) were matched on age (± 3 years) with up to two patients who underwent polypectomy but were not receiving AC (non-AC group). Data were extracted from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(43 citation statements)
references
References 16 publications
3
40
0
Order By: Relevance
“…Although anticoagulation has been linked to postpolypectomy bleeding [3,38,39,42], no studies have found any statistically significant association between intravenous heparin infusions and post-PEG bleeding.…”
Section: Discussionmentioning
confidence: 95%
“…Although anticoagulation has been linked to postpolypectomy bleeding [3,38,39,42], no studies have found any statistically significant association between intravenous heparin infusions and post-PEG bleeding.…”
Section: Discussionmentioning
confidence: 95%
“…9 11-14 Routine discontinuation of warfarin therapy may therefore be considered necessary in most colonoscopy services. Even when temporarily discontinued, warfarin therapy is associated with an increased risk of post-polypectomy bleeding (PPB) 15 and patients should be advised of this.…”
Section: Warfarinmentioning
confidence: 99%
“…Their practice was to stop warfarin 4 days prior to colonoscopy and restart it immediately after the procedure. Friedland et al [9] reported a 0.8% incidence of major post-polypectomy bleeding requiring transfusion while holding warfarin 36 h before the procedure. Little to no information is available on the management of clopidogrel therapy, although some studies suggest that there may be a higher risk of bleeding when aspirin and clopidogrel are being used simultaneously [13].…”
Section: Discussionmentioning
confidence: 98%
“…The risk of post-polypectomy bleeding has been found to be higher in patients receiving anticoagulation despite interruption of therapy [8]. However, Friedland et al [9] found a very low risk of bleeding 0.8% when small polyps (less than 1 cm) were removed in patients without interruption of anticoagulation. Recent studies have found no increased risk of post-polypectomy bleeding in patients on NSAIDs and aspirin [4,7].…”
Section: Introductionmentioning
confidence: 97%